2016
DOI: 10.14737/journal.jap/2016/3.2.32.48
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 16s rDNA based Analysis of some Hard Ticks Belonging to Genus Hyalomma Koch, 1844 (Acari: Ixodidae)

Abstract: | A molecular analysis of mitochondrial 16s rDNA sequences of hard ticks belonging to genus Hyalomma from Haryana (India) and those available in genbank database was done so as to resolve inter-relationships between members of genus Hyalomma. For this a total of eighty one 16s rDNA sequences belonging to 16 taxa were subjected to molecular and phylogenetic analysis which was conducted in MEGA6 and Beast 1.8.0 software. Phylogenetic relationships were inferred using the bayesian, maximum likelihood (ML) and nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As shown in the results, the Maximum Likelihood tree generated in the present study recorded several clusters (groups) of the mitochondrion 16S rRNA gene sequences, indicating high divergence of the gene sequences of hard ticks (21,22,23) present in this wildlife-livestock interface ecosystem. In that way, clusters of similar sequences represent species clearly separated from other clusters (species) (24,25,26).Therefore, this is a re ection of high biological diversity of ticks within Ixodidae (hard ticks) (27,28,29) present in this wildlife-livestock interface ecosystem. (30) or misidenti cation among the species (31,32).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown in the results, the Maximum Likelihood tree generated in the present study recorded several clusters (groups) of the mitochondrion 16S rRNA gene sequences, indicating high divergence of the gene sequences of hard ticks (21,22,23) present in this wildlife-livestock interface ecosystem. In that way, clusters of similar sequences represent species clearly separated from other clusters (species) (24,25,26).Therefore, this is a re ection of high biological diversity of ticks within Ixodidae (hard ticks) (27,28,29) present in this wildlife-livestock interface ecosystem. (30) or misidenti cation among the species (31,32).…”
Section: Discussionmentioning
confidence: 89%
“…As expected, the mean genetic distances recorded in the present study increased with higher taxonomic ranking; 0.01 ± 0.00, 0.06 ± 0.01 and 0.11 ± 0.01 for intraspecies, intragenus and overall tick community respectively. This makes the mitochondrion 16S rRNA gene to be a good marker for supraspeci c differentiation and mainly, for taxa grouping purposes (28,29,39). According to Ros et al (2007) (40), DNA barcoding assumes that the genetic distances between species are greater than within species.…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with some studies using mt 12S rDNA, 16S rDNA or ITS, in which Hyalomma spp. shown high divergence distance and low bootstrap value [25,26]. As many results indicated that there is a high diversity in hard ticks [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…anatolicum anatolicum and H. anatolicum excavatum were subspecies until Apanaskevich and Horak [60] raised those to the rank of species namely Hyalomma anatolicum Koch 1844 and Hyalomma excavatum Koch 1844 based on morphological characters. In this context, a recent study of Hosseini et al, [61] using morphometric methods on male specimens of Hyalomma anatolicum have shown polymorphism in the important taxonomic characters and have recommended more studies on related species for proper identification of species. According to the present analysis there is very strong support for Anatolicum clade of Hy.…”
Section: Anatolicum Groupmentioning
confidence: 99%